Analysis of the interleukin-6 gene promoter polymorphisms in Czech patients with chronic periodontitis - Holla, Lydie Izakovicova; Fassmann, Antonin; Stejskalová, Andrea; Znojil, Vladimír; Vanĕk, Jiri; Vacha, Jiri (Journal of periodontology, 2004)
BACKGROUND: Chronic periodontitis is an inflammatory disease, which is a major cause of tooth loss. The proinflammatory cytokines interleukin-1 (IL-1) and interleukin-6 (IL-6) are key regulators of the host response to microbial infection and major modulators of extracellular matrix catabolism and bone resorption. The purpose of this study was to investigate the associations of chronic periodontitis with IL-6 gene polymorphisms (at positions -597 [G/A], -572 [G/C], and -174 [G/C]). METHODS: We analyzed allele, genotype, and haplotype distributions of the IL-6 promoter variants in a case-control study involving 148 patients with chronic periodontitis and 107 unrelated controls. RESULTS: Our results showed significant differences in the distributions of alleles and genotypes of the IL-6 (-572 G/C) polymorphism between patients and the control population (chi2 = 10.393, P= 0.001, P(corr) < 0.01). The difference was due to the underrepresentation of the -572 G/C heterozygotes in patients (6.1%) compared to controls (19.6%). Although no variant "CC" homozygotes were detected in our cases and controls, heterozygosity protected against chronic periodontitis, representing a 73% reduction of risk (odds ratio [OR] = 0.27, 95% confidence interval: 0.12-0.61) compared to wild-type homozygotes. However, there were no significant differences in genotype or allele frequencies between both groups for IL-6 -597 G/A and -174 G/C polymorphisms. CONCLUSION: This study is the first, to our knowledge, suggesting that the -572 G/C polymorphism of the IL-6 gene may be one of the protective factors associated with lower susceptibility to chronic periodontitis.
Keywords: dospělí; Polymorphism, Restriction Fragment Length; parodontitida; odds ratio; alely; studie případů a kontrol; Promoter Regions, Genetic; Humans; Polymerase Chain Reaction; Genetic Predisposition to Disease; genetická predispozice k nemoci; lidé středního věku; Gene Frequency; Periodontitis; metoda Monte Carlo; Middle Aged; kouření; Chronic Disease; Monte Carlo Method; Smoking; mužské pohlaví; Adult; heterozygot; promotorové oblasti (genetika); polymorfismus délky restrikčních fragmentů; polymerázová řetězová reakce; frekvence genu; chronická nemoc; ženské pohlaví; Female; interleukin-6; lidé; Case-Control Studies; Heterozygote; Odds Ratio; Male; Interleukin-6; Alleles